Gestión de calidad a través de políticas y procedimientos para el proceso educativo de las personas privadas de libertad matriculadas en la unidad educativa “Monseñor Leonidas Proaño” del centro de rehabilitación social regional sierra centro del norte. Manual de procedimientos. - Aguilera Ríos, Marina De Lourdes (2017)
The project aims to solve a problem related to the non existence of specific procedures for the development of educational activities in the context of deprivation of liberty. In order to solve the aforementioned problem, the objective is to strengthen administrative management through procedures for the educational área. The Administrative is in charge of the planning, organization, direction and control of the resources of a company or institution with the purpose of obtaining greater efficiency and the maximum possible profit. Management, on the other hand, is in charge of the assignment of responsibilities to carry out actions programmed for the accomplishment of a process with the purpose of achieving the institutional objectives. Process management is a discipline organization that helps the management of the company or institution to identify, represent, design, formalize, control, improve and make more productive the processes of the organization to achieve customer confidence.....